Strategies for liver transplantation during the SARS‐CoV‐2 outbreak: Preliminary experience from a single center in France. Issue 11 (5th July 2020) - Muller, Xavier; Tilmans, Gilles; Chenevas‐Paule, Quentin; Lebossé, Fanny; Antonini, Teresa; Poinsot, Domitille; Rode, Agnès; Guichon, Céline; Schmitt, Zoé; Ducerf, Christian; Mohkam, Kayvan; Lesurtel, Mickaël; et al.
Abstract : Liver transplantation (LT) during the ongoing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic is challenging given the urgent need to reallocate resources to other areas of patient care. Available guidelines recommend reorganizing transplant care, but data on clinical experience in the context of SARS‐CoV‐2 pandemic are scarce. Thus, we report strategies and preliminary results in LT during the peak of the SARS‐CoV‐2 pandemic from a single center in France. Our strategy to reorganize the transplant program included 4 main steps: optimization of available resources, especially intensive care unit capacity; multidisciplinary risk stratification of LT candidates on the waiting list; implementation of a systematic SARS‐CoV‐2 screening strategy prior to transplantation; and definition of optimal recipient‐donor matching. After implementation of these 4 steps, we performed 10 successful LTs during the peak of the pandemic with a short median intensive care unit stay (2.5 days), benchmark posttransplant morbidity, and no occurrence of SARS‐CoV‐2 infection during follow‐up. From this preliminary experience we conclude that efforts in resource planning, optimal recipient selection, and organ allocation strategy are key to maintain a safe LT activity. Transplant centers should be ready to readapt their practices as the pandemic evolves. Abstract : The authors report successful liver transplantion during the peak of the SARS‐CoV‐2 outbreak, highlighting optimal organ allocation, recipient screening and selection strategies, and resource planning strategies to safely maintain transplant activity during the pandemic.